policy of the United States of America Czechoslovakia (19391918) (Journal of the College of Basic Education, 2023)
The history of the United States of America is linked to the history of Europe in a dialectical relationship, especially inThe first three centuries, from the date of discovery 1494 until the date of independence 1783In any case, the two dates can be separated from each other due to important considerations, the most important of which is thatThe roots of the population of the United States today are European roots, and the language used there is the language ofEuropean, and many of the European political events have clear repercussions on the arena.politics within the United States. And despite following the policy of isolation or what has been known as the Monroe Doctrine sinceThe year 1823, ie distancing from the affairs and problems of the European continent.The United States chose isolation voluntarily, desiring to be unique to the two continents.the Americas alone and in order to strengthen its economic, political and military efforts to support its presencematerial and moral to the north and south of the borders of her country, despite declaring that the reason forIts choice was the Napoleonic Wars (1804-1815) and the human and natural disasters it caused.However, it used to intervene in Europe or the rest of the world from time to time in service.For its national, economic and missionary interests, and there are many examples of that at times with the Ottoman state.Sometimes with China and others in Africa, and so on.Although she abandoned the principle of the 1917 Monroe when she seriously participated in theAn effective contribution to achieving victory for the Allies in the First World War (1914-1918).She participated in a delegation similar to that of political figures in the Peace Conference in Paris 1919, but sheIt returned once again to the principle of isolation after the US Congress tied the hand of the president of his country and the role ofWilson Woodroul Thomas (1921-1913 / 1921-1859) in politics.This isolation remained until 1941 when President Franklin Delano Roosevelt D.Franklin Roosevelt (1945-1933/1945-1882) of public opinionThe American need to be present on the European political scene outside the United StatesHe was helped by the Japanese attack on Pearl Harbor on December 7.